Empowering Educators through CPD: Enhancing Teacher Competencies in the Era of the Independent Curriculum - Alief Firmansyah; Beni Desnora; Aldo Pratama; Muazza Muazza; Aprillitzavivayarti Aprillitzavivayarti (Nurul Jadid University, 2025)
This study examines the role of Continuing Professional Development (CPD) as a strategy for developing teacher competency in the context of the Independent Curriculum. The study was conducted using a desk study method, reviewing scientific literature, research reports, and relevant education policy documents, particularly those published between 2015 and 2024. The analysis shows that Continuing Professional Development (CPD) serves as a strategic instrument for continuously improving teachers' pedagogical, professional, social, and personal competencies. Continuing Professional Development (CPD) not only helps teachers adapt to curriculum changes, such as differentiated and project-based learning, but also enhances professionalism, motivation, and learning innovation. However, the implementation of Continuing Professional Development (CPD) in Indonesia faces challenges, including time constraints, inconsistent material quality, varying teacher motivation, and disparities in access across regions. Therefore, optimizing Continuing Professional Development (CPD) requires targeted strategies, such as tailoring programs to teachers' real needs, utilizing digital technology, strengthening collaboration through Professional Learning Communities (PLC), and ongoing monitoring and evaluation.